Design of dual band notched ultra wideband antenna using (U-W) shaped slots - Ahmed, Mohammed Shihab; Islam, Md Rafiqul; Khan, Sheroz (Asian Research Publishing Network (ARPN), 2015)
The Ultra-Wideband (UWB) communications have become a hot topic for researchers. To mitigate the interference with the existing WiMAX (3.3 GHz – 3.6 GHz) and WLAN (5.15 GHz – 5.825 GHz) systems, a Dual BandNotched antenna for Ultra-Wideband applications is proposed. The antenna consists of rectangular patch, a 50 Ω Microstrip line and partial grounding. By etching a nested inverted U-Shaped and W-Shaped slots in the radiating patch, band rejection filtering properties for WiMAX and WLAN were achieved. The simulation results were obtained using electromagnetic simulation software (CST Microwave Studio). Simulation results shows that the return loss for the frequency band from 2.87 GHz to 11.48 GHz is below -10dB, which is considered operational. The antenna also has bandnotched functions in the range from 3.24 GHz to 3.65 GHz and from 5.01 GHz to 6.01 GHz. Thus the interference between WiMAX, WLAN and Ultra-Wideband can be avoided.